The Effect of Hyperbaric Oxygen Therapy on Rectal Ulcers after Argon Plasma Coagulation - Laranjo,Ana (2021)
Abstract: Chronic radiation proctitis usually develops 3 months after therapy. Despite the lack of standard guidelines regarding treatment, argon plasma coagulation is often a safe and effective endoscopic therapy. However, rectal ulcers are a common complication after argon plasma coagulation. Nevertheless, most patients are asymptomatic and do not require additional monitoring or treatment. We report a case of an argon plasma coagulation-induced ulcer with relevant symptoms and refractory to medical treatment. The patient was treated with hyperbaric oxygen therapy and had complete resolution of the rectal ulcer. Hyperbaric oxygen therapy has shown efficacy in severe chronic proctitis and radiation-induced rectal ulcers, but no clinical report has ever been published on using hyperbaric oxygen therapy for ulcers after argon plasma coagulation. In this case, hyperbaric oxygen therapy was an effective alternative option and can be considered in patients with refractory argon plasma coagulation-induced rectal ulcers.